BEAUTY IS… - Lasithiotaki, Nina (Design/Arts/Culture, 2023)
Walter Benjamin aptly describes the dual role of photography, since its invention, saying that “photography stakes a claim to art as soon as it appears as a commodity”. Although fashion has become the subject of significant philosophical and sociological study over the past 150 years, it continues to be a taboo, or merely too lowly a subject for academic consideration – even in modern–day cultural studies. The reason is clear: fashion does not pose an argument; it entices and seduces, constantly looking for a new aesthetic paradigm that will embody the eternal polytheism of Beauty. Photographer Julia Hetta adopts many of the tools and practices of classical painting to capture the paradox and ambiguity of the concept of Beauty, which Victor Hugo likens to Death, noting that: “Death and beauty are two things profound, so of dark and azure, that one might say that they were two sisters terrible and fecund, possessing the one enigma, the one secret.” Hetta illustrates the dualism of the modernist subject with appeals to the imaginary of an insurmountable innocence and purity, as this is captured in depictions of the classical ideal; and precisely therein lies the originality of her gaze. She develops a personal style in photography, featuring strong elements of drama and theatrics. She illustrates the current, the innovative, the radical in the field of human presence and clothing, recalling the cultural deposits of times past, but also imbuing her creations with new rules that detect a subjective and complex beauty.